Playing position influences the relative age effect in senior rugby union - Kearney, P.E. (Science & Sports, 2017)
Objective: To establish whether playing position influenced the existence of the relative age effect (RAE) in senior rugby union. Summary of facts and results: The birth dates and playing position of 1991 senior French rugby union players registered during the 2014/15 season were obtained from an on-line statistics database. The distribution of player births was compared with the distribution of births in the general French population across the period in question. Results indicated that a RAE existed for forwards but not backline players. Back row forwards in particular showed a pronounced RAE. Conclusion: The existence of the RAE within senior French rugby union is influenced by player position.